THE ANTHROPOLOGICAL DIMENSION OF VIRTUAL REALITY - Skyba, Oksana (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Today, the widespread use of information and communication technologies gives rise to virtual reality, which acquires a new ontological and anthropological status. The aim of the article is an attempt at philosophical reflection on the anthropological dimension of virtual reality in the context of the correlation between the virtual and the real. Research methods. The theoretical and methodological basis of this work is a system of scientific research methods and principles: analysis and synthesis, abstraction, as well as the method of the unity of the historical and the logical, which make it possible to explore the mechanism of interaction between the real world and virtual reality, society and virtual reality. Research results. Throughout the 19th–20th centuries, the idea of "virtual reality" continued to develop as the idea of a certain special, intermediate state. In various fields of knowledge, these states differed across different objects—for example, in physics, it referred to a special state of micro-objects; in psychology, to a special state of subjectivity (including dreams, fantasies, altered states of consciousness, the reality of computer games, etc.); and in computing, to a specific mode of computer operation. Thus, it is precisely the ambiguity of the concept that has led to its wide application—from Niels Bohr’s "virtual particles" and his complementarity principle to the world of "virtual reality" created by information technologies. The concept of virtual reality acquires an entirely new meaning with the advent of computers and the development of the Internet. Discussion. In virtual reality, vast and ever-changing flows of information determine its nature. Immersed through immersive technologies and complex feedback systems, individuals experience the dissolution of spatial and temporal boundaries, the erosion of cultural differences, and the emergence of new values, behaviors, language, and worldview patterns. This expansion of human living space in the information age signals a new mode of existence for both individuals and society. Meeting this challenge and fostering harmonious development requires cultivating intellectual abilities and value orientations rooted in traditional ethics. Conclusions. Virtual reality allows man to overcome the boundaries of space and time, provoking the creation of new value orientations, new models of behavior, and worldview stereotypes. The virtualization of part of a person's living space creates a new way of life for both the individual and society, expands human capabilities, and becomes the foundation for a new type of culture..